Efeito da pulverização com turboatomizadores em diferentes condições operacionais no controle de ácaros em citros - Raetano, Carlos Gilberto [UNESP]; Matuo, Tomomassa [UNESP] (Sociedade Entomológica do Brasil, 1999)
Estudou-se o efeito das pulverizações de azocyclotin por turboatomizadores Jacto Arbus 2000/Export e Arbus 2000/850, sob diferentes condições operacionais, no controle do ácaro purpúreo, Panonychus citri (McGregor), e da leprose, Brevipalpus phoenicis (Geijskes); e de Arbus 2000/Export contra o ácaro da falsa ferrugem, Phyllocoptruta oleivora (Ashmead). Foram instalados três experimentos em pomares de citros (var. Valência) no período de 1994/95. O acaricida azocyclotin na dose 25 g i.a. / 100 litros d'água foi eficiente por 52 dias no controle de B. phoenicis e por 28 dias contra P. oleivora. Variações nas condições operacionais dos turboatomizadores não influenciaram no controle dos ácaros pragas. O produto azocyclotin pulverizado a 75% da dosagem comercial com 35 bicos do tipo JA-2 (Jacto), a 3,6 km/h e na pressão de 2070 kPa proporcionaram níveis de controle equivalentes aos obtidos com 100% da dosagem comercialmente recomendada desse acaricida, até 16 dias, quando aplicado com o turboatomizador Jacto Arbus 2000/Export no controle de P. citri.

The spray from airblast ground sprayers to different operational conditions were studied in mite control. Three experiments were carried out in `Valencia' commercial citrus orchard, during november /94 to november /95. Two of them using Jacto Arbus 2000/Export and Jacto Arbus 2000/850 airblast sprayers and the third one using Arbus 2000/Export. The efficacy of azocyclotin spray were evaluated on citrus rust mite Phyllocoptruta oleivora (Ashmead), leprosis mite Brevipalpus phoenicis (Geijskes) and red spider mite Panonychus citri (McGregor). The dosage of 25 g a.i. of azocyclotin per 100 litre water was efficient during fifty-two and twenty-eight days after spraying on the control of mites B. phoenicis and P. oleivora, respectively. Different operational conditions did not permit to identify significative differences between treatments on the initial mite control. The spraying of azocyclotin at 75% of commercial dosage with thirty five JA-2 nozzles type (Jacto) at 3.6 km/h and 2070 kPa of working pressure showed equivalent control levels up to sixteen days when compared with 100% of conventional dosage used for red spider mite control with the Arbus 2000/Export airblast sprayer.
Operational conditions of airblast sprayers in the spray on citrus mite control
Keywords: Acari; azocyclotin; controle químico; pulverização; citros; Acari; azocyclotin; chemical control; spraying; citrus orchard